ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA MEMILIH PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNS (STUDI PADA ANGKATAN 2014 DAN 2015) - Testian Yushli Ana; Sunarto Sunarto; Sudarno Sudarno (Department of Economics Education, Universitas Sebelas Maret, 2018)
This study purpose to determine the factors that influence the decision of the students chose Economic Education Studies Program of FKIP UNS in force in 2014 and 2015. This research is a survey method. The analysis used in this research is factor analysis. The population in this study were students Economic Education Studies Program class of 2014 and 2015, amounting to 122 students. The sample in this study was 115 respondents in the manner five times 23 the number of overall indicators. The sampling technique used in this research is purposive sampling. The data used are primary data obtained by distributing questionnaires. In this study, the independent variables used are the social variables, personal, motivation, references, promotion, facilities, reputation, and the cost of the dependent variable student's decision choosing Economic Education Studies Program of FKIP UNS .The results of this study indicate that there are four factors that influence the decision of students choosing Economic Education Studies Program of FKIP UNS. These factors are: (1) factors image factor with eigenvalues highest of 1,585 and variants 19.808%, (2) social factors with a variant of 15.126%, the cost factor with a variant of 13.881%, and the reference factor with a variant of 12.714%, with total variance can be explained amounted to 61.530%.